Scandal : Infamous Gay Controversies of the Twentieth Century. - Vargo, Marc E. (Taylor and Francis, 2013)
Examine the cornerstone incidents of modern gay political history!Scandal: Infamous Gay Controversies of the Twentieth Century is a compelling and thorough examination of same-sex controversies that range from accusations of obscenity and libel to espionage, treason, murder, and political dissent, with penalties that included censorship, imprisonment, deportation, and death. In each case, scandal brought the subject of homosexuality into public view in an explosive, sensational manner, stalling (and sometimes reversing) any progress made by the gay and lesbian community in mainstream.